Society of Behavioral Medicine position statement: elementary school-based physical activity supports academic achievement - Buscemi, Joanna (Transl Behav Med, 2014)
The Society of Behavioral Medicine (SBM) urges elementary schools to provide children with ample opportunities to engage in physical activity during school hours. In addition to promoting overall child health, physical activity also supports academic achievement. In addition to improving their aerobic fitness, regular physical activity improves cognitive function, influences the brain, and improves mood in children. Better aerobic fitness and physical activity are associated with increased grade point averages and standardized test scores. Despite the documented relationship between physical activity, fitness, and academic achievement, few schools have implemented physical activity as a tool to improve academic performance. SBM recommends that elementary schools provide children with the recommended 60 min of moderate-to-vigorous physical activity during school hours. Further, SBM urges schools to work with the local school districts and state education departments to mandate minimum physical activity time for elementary school physical education.